(untitled) (American Journal of Life Science and Innovation, 2023)
Type I and Type 2 diabetes are the two main types with types diabetes accounting for the majority (>85%) of total diabetes prevalence. Both forms of diabetes can lead to multisystem complications of microvascular endpoints including retinopathy, nephropathy and neuropathy and microvascular endpoints including is cadmic heart disease, stroke and peripheral vascular disease. The premature morbidity, mortality, reduced life expectancy and financial and other others costs of diabetes make if an important public health condition. The aim of this study was to observe the clinical condition and consequences patients with diabetes mellitus in Bangladesh. A descriptive cross-sectional study was conducted for the study. Data are collected from BIHS General Hospital. The results showed that, among 100 patients 20% patient was affected by Type-1 Diabetes Mellitus (DM) and 80% patient was affected by Type-2 Diabetes Mellitus (DM). In comparison between Type-1 and Type-2 DM patient’s result showing that Fasting Plasma Glucose (FPG) and 2 hour ABF plasma Glucose range is slightly high in Type-1 DM than Type-2 DM. On the other hand, Creatinine, HbA1C, TSH, Total cholesterol (TC), Triglycerides (TG), HDL ranges are increased in Type-2 DM patient. In this study males are affected 62% and females are 32%. So the ratio between male and female is 2:3. More patients were found in the age between 50-60 years and has risk among 40-50 years. Eating the right foods and adopting other life style behaviors that promotes healthy blood sugar and insulin levels will give you the best chance at avoiding diabetes.